Functional characterization of testis-brain RNA-binding protein, TB-RBP/Translin, in translational regulation - Kanako OYAMA; Tadashi BABA; Shin-ichi KASHIWABARA (The Society for Reproduction and Development, 2020)
Testis-brain RNA-binding protein (TB-RBP/Translin) is known to contribute to the translational repression of a subset of haploid cell-specific mRNAs, including protamine 2 (Prm2) mRNA. Mutant mice lacking TB-RBP display abnormal spermatogenesis, despite normal male fertility. In this study, we carried out functional analysis of TB-RBP in mammalian cultured cells to understand the mechanism of translational repression by this RNA-binding protein. Although the amino acid sequence contained a eukaryotic translation initiation factor 4E (EIF4E)-recognition motif, TB-RBP failed to interact with EIF4E. In cultured cells, TB-RBP was unable to reduce the activity of luciferase encoded by a reporter mRNA carrying the 3'-untranslated region of Prm2. However, λΝ-BoxB tethering assay revealed that the complex of TB-RBP with its binding partner, Translin-associated factor X (TRAX), exhibits the ability to reduce the luciferase reporter activity by degrading the mRNA. These results suggest that TB-RBP may play a regulatory role in determining the sequence specificity of TRAX-catalyzed mRNA degradation.